Growth-finance nexus in oil abundant GCC countries of MENA region - Mohammad Imdadul Haque; Bashir Umar Faruk; Mohammad Rumzi Tausif (Cogent Economics & Finance, 2022)
Economic growth and financial development are intrinsically related. Literature provides evidence that economic growth leads to financial development and financial development also leads to economic growth. The study analyzes this association between economic growth and financial development considering institutions for countries with substantial oil rents. The study uses the Pedroni test for cointegration, Granger causality, Ordinary Least Squares (Panel, Fully Modified, and Dynamic) methods to study the relationship on a panel data of six countries from 2000 to 2019. The study proceeds with the hypothesis that economic growth leads to financial development in countries having oil rents. The study finds that economic growth has a significant positive impact on the financial sector development of the GCC countries and not vice versa. The study also reports that poor institutional quality constraints the contribution of oil rents to financial development. The results imply that in countries accruing oil rent, the quality of institutions needs to be improved for furthering the cause of financial development. Although the study advances the empiricism on the link between economic growth and financial development, incorporating institutions and oil rents is the study's novelty.
Keywords: F43; G00; C3; 330; Economic growth; financial development; oil rents; institutions